The behavioural effects of enkephalin analogues injected into the ventral tegmental area and globus pallidus. - Joyce, E; Koob, G; Strecker, R; Iversen, S; Bloom, F (1981)
Two stable analogues of enkephalin D-Ala2-Met5-enkephalinamide (DAMA) and D-Ala2,D-Leu5-enkephalin (DADLE) injected bilaterally into the ventral tegmental area (VTA) induced locomotion, characterized by bursts of morphine-like activity. The response of DADLE was blocked by systemic-alpha-flupenthixol (0.2 mg/kg) and naloxone (1 mg/kg). At higher doses of enkephalins in the VTA, stereotypy behaviour involving gnawing, became apparent. When injected bilaterally into the globus pallidus (GP), both analogues induced a dose-dependent increase in locomotor activity but stereotypy was not observed. The locomotor behaviour induced by DADLE was blocked by naloxone but not by alpha-flupenthixol. These results suggest that naloxone-sensitive opiate receptors modulate, at a number of different sites, the neural pathways involved in the expression of behavioural activity.